Machado de Assis: do teatro. Textos críticos e escritos diversos de João Roberto Faria - Azevedo, Elizabeth R. (Sala Preta, 2008)
Resenha: Machado de Assis: do teatro. Textos críticos e escritos diversos de João Roberto Faria